Pattern-reversal visual-evoked potentials in children with migraine and other primary headache: evidence for maturation disorder? - Oelkers-Ax, Rieke; Bender, Stephan; Just, Ulrike; Pfüller, Ute; Parzer, Peter; Resch, Franz; Weisbrod, Matthias (Pain, 2004)
Recently, evidence for a disturbed maturation of cerebral information processing in migraine came from studies investigating the auditory-evoked contingent negative variation and the auditory-evoked potential from childhood to adulthood. This study is to clarify whether age-dependent development is altered also for the processing of visual stimuli in migraine. Components of pattern-reversal visual-evoked potentials at four different spatial frequencies (which can preferentially activate the magno- and the parvocellular visual system) were compared between children aged 6 and 18 years with primary headache (N=123; 67 migraine without aura, MO; 32 migraine with aura, MA; 24 tension-type headache, TH) in the headache-free interval and healthy controls (N=82). Children were divided into two age groups: 6-11 years (pre- and early puberty) and 12-18 years (late and post-puberty). Age-dependent development was normal for N80 and P100 latency in children with primary headache, but altered for N135 latency as indicated by a significant interaction among the factors diagnosis, spatial frequency and age group (P<0.01). In headache-free controls, N135 latency reduction between pre- and post-puberty age was most pronounced at high spatial frequency. The main ‘decline’ of N135 latency with increasing age was shifted to lower spatial frequencies in the headache subgroups. The results give evidence that maturation of visual processing is partly disturbed in migraineurs.